Application of Hibah, Umra and Ruqba in joint tenancy with right of survivorship: an analysis - Rahman, Md. Habibur; Ghazali, Puspa Liza; Abdullah, Md. Faruk; Osmani, Noor Mohammad (USIM Press, Universiti Sains Islam Malaysia, 2018)
Umra and Ruqba are the two forms of donation that were practised and familiar in the pre-Islamic period. Umra means making a donation subject to the life of the beneficiary or the donor with a condition that the property should be returned back to the donor after the demise of the beneficiary. It also means a temporary provision which refers to the life of any party of hibah arrangement, either the hibah giver or the recipient. Ruqba, on the other hand, is a donation where the beneficiary possesses the donation after the death of the donor, provided that the beneficiary survives upon that. Thus, umra and ruqba both are the forms of conditional donation while in the earlier the donation comes back to the donor after the demise of the beneficiary and in the later the beneficiary owns the donation after the demise of the donor if he survives up till that. The conditional hibah is valid provided that the related provision shall be adjustable and consistent with the contract and shall it not go to beyond shari’ah principles. The arrangements of umra and ruqba, being the conditional forms of hibah, are valid, albeit the condition of returning back the donated item to the donor is invalid. The application of umra and ruqba donations are valid as the underlying ground for the survivorship principle of joint tenancy contract, which would facilitate housing for the Muslim couples being compliant with shari’ah rules and regulations.